Experimental studies of energy efficiency of heat pump equipment for hot water supply and air conditioning systems in apartment buildings. Issue 4 (December 2021) - Vasilyev, Gregory; Gornov, Victor; Kolesova, Marina; Leskov, Vitaliy; Silaeva, Victoria; Marchenkova, Svetlana; Dmitriev, Alexander
Abstract: Experimental studies of this article are aimed at solving the problem of reforming the housing and communal services of Russia through rational integration of non-traditional energy sources and secondary energy resources into the energy balance of buildings and structures. An important component of the work was the creation and development of industrial production of reliable competitive heat pump systems of a new generation, cogenerating heat energy and cold in an autonomous mode and providing energy savings of at least 50% due to the combined use of low-potential thermal energy of the soil, the atmospheric air and the exhaust air of ventilation systems for hot water supply and air conditioning systems of apartment buildings.